PRAKARSA SEKOLAH DALAM MENINGKATKAN KEEFEKTIFAN BELAJAR DAN PEMBELAJARAN STUDI KASUS DI SEKOLAH DASAR NEGERI 3 DAUHWARU, JEMBRANA, BALI - Samsul Hadi (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2015)
Abstract: In the school environment, the initiative may come from regional leaders, principals, teachers, learners, parents and the community through school councils and committees. In general, the initiative is intended to improve the quality of education through the renewal in various components of the educational process. The initiative forms are very diverse, because it depends on the culture and school conditions. The focus research is how to shape school initiative in improving the effectiveness of teaching and learning?, what are the factors that support and hinder the realization of school initiatives to improve the effectiveness of teaching and learning?, how the steps taken to improve the support and overcome these barriers? This study used a qualitative approach with case study design. Collecting data in this thesis using the technique of in-depth interviews, participatory observation and documentation. From the data analysis found that: (1) school initiative in improving the effectiveness of teaching and learning at SDN 3 Dauhwaru; (2) While the factors inhibiting school initiative in improving the effectiveness of teaching and learning at SDN 3 Dauhwaru is local government policy and conditions of teachers at SDN 3 Dauhwaru Jembrana, Bali; (3) the efforts made to improve the support and overcome barriers to school initiative in improving the effectiveness of teaching and learning at SDN 3